1981
DOI: 10.1063/1.442611
|View full text |Cite
|
Sign up to set email alerts
|

Absolute electron impact ionization cross section from threshold up to 180 eV for N2O+e→N2O++2e and the metastable and collision induced dissociation of N2O+

Abstract: Electron impact ionization of nitrous oxide was studied as a function of electron energy up to 180 eV. A double focusing mass spectrometer in combination with an improved electron impact ion source (Stephan et al.) was used, alleviating the problems of ion extraction from the source and the transmission of the extracted ions through the mass spectrometer system. Relative partial ionization cross sections were measured for the process N2O+e→N2O++2e. These cross sections were calibrated absolutely by normalizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The production of this ion starts at about 12.3 eV, reaches a maximum around 100 eV and smoothly decreases as energy increases to 1000 eV. The solid diamonds represent the measurements of Mark et al [1981] from threshold to 180 eV. Although their "ionization efficiency curve" has a shape similar to ours, the magnitude of their cross-section is about 30% lower than the present value at 100 eV.…”
Section: In Figure 3 Curve 1 Represents Our Values Of Total Ionizatisupporting
confidence: 52%
“…The production of this ion starts at about 12.3 eV, reaches a maximum around 100 eV and smoothly decreases as energy increases to 1000 eV. The solid diamonds represent the measurements of Mark et al [1981] from threshold to 180 eV. Although their "ionization efficiency curve" has a shape similar to ours, the magnitude of their cross-section is about 30% lower than the present value at 100 eV.…”
Section: In Figure 3 Curve 1 Represents Our Values Of Total Ionizatisupporting
confidence: 52%
“…Märk et al 27 measured partial ionization cross section of N 2 O for the production of N 2 O ϩ by electron impact. Their peak cross section is 1.49ϫ10 Ϫ20 m 2 at Tϭ110 eV.…”
Section: H Nitrous Oxide (N 2 O)mentioning
confidence: 99%
“…However, for the doubly charged fragment ions (N 2+ + O 2+ ), the present data are found to be higher by almost a factor of four compared to the relative ionic fraction reported earlier at a very low impact energy. A large number of studies [1][2][3][4][5][6][7][8] have shown the importance of total and partial ionization cross sections (PICSs) of various molecules relevant, in particular, to our planetary and interstellar space, plasma physics, and astrophysics. Nitrous oxide (N 2 O), also called laughing gas, is a very important molecule that can cause biological as well as environmental changes.…”
mentioning
confidence: 99%